A strategy for labor performance improvement for floor tiling work in single storey buildings in Abuja, Nigeria - Idiake, J.E.; Kabir, B.; Shittu, A.A. (Penerbit UKM, 2015)
This paper examined labor productivity of floor tiling works in selected construction sites. Sixty one (61) sites were visited for the purpose of collecting data. The construction sites chosen for this study were ongoing one storey buildings in Abuja, Nigeria. Data used for the study were obtained using daily method of data collection which has the advantage to capture both quantity and time inputs. A total of 737 data points were collected for the floor tiling activity in all the sites. From these data, the study variables (cumulative productivity, baseline productivity, coefficient of variation and project performance index) were computed using conceptual (site-based) model of labor productivity measurement and the results revealed that many of the projects studied had low performance rating while few of projects performed well. A simple regression and correlation analyses were used to determine relationships of the research variables. The result showed that the coefficient of correlation between coefficient of labor productivity variability and performance index was found to be 0.588 which is significant at 0.01 confidence level. The coefficient of determination (R) was calculated to be 0.44. This showed that 44% variation in crew performance is accounted for by variability in labor productivity. It was suggested that crew performance in tiling work can be improved by moderating or curtailing variability in labor productivity.